(3QSGdI YQGbjIs - (3YHO Gddg Hf eMeO GdcQOj GdHJhTj , CHh eMeO,J (B1221 (3g` s ((3GdSeGhi s)
(3ChdgG (B:s
(3Efi CMf GdYQGb hde Gcf dGef QUGaJg hdG ef cQNg s
(3BNQgG (B:s
(3heeG cJHg GdCOjH aGVd NGf GdcQhSi ddSjO SYjO GdgeOGfi Mjf JRhL cQOjI ef bQi geOGf jbGd dgG hQOhJjf SdGei Ydi Jdc GdeYGgO CfgG TQjYI hQOi Ch egH TeGdi s
(3CQSdgG ef GdCMSGA SfI (B1217(3g Edi YHOGddg Hf UHZI Gddg ai HZOGOs
(3VefgG Tchi GdOgQ hcSGO GdCOHs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B131 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B138 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B487s
Keywords: (3GdCOHs